2005
DOI: 10.1111/j.1744-697x.2005.00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of fermented juice of epiphytic lactic acid bacteria on the fermentative quality of guineagrass (Panicum maximum Jacq.) silage

Abstract: Two experiments were conducted to evaluate the effects of fermented juice of epiphytic lactic acid bacteria (FJLB) prepared with glucose, sucrose or molasses as additives on the fermentative quality of guineagrass silage. The numbers of lactic acid bacteria (LAB) in all FJLB increased from 105 c.f.u. mL−1 to 108−109 c.f.u. mL−1 after 2 days of anaerobic incubation. FJLB mixed with 3% of the three sugar substrates were added at various volumes (0.2, 0.5 and 1%[v/w]) in experiment 1. As the volume of FJLB added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 15 publications
4
24
0
1
Order By: Relevance
“…This is partly due to restricted fermentation, a lack of sufficient energy for optimal multiplication and growth of lactic acid bacteria. The present result confirms previous findings on the benefit of molasses addition when ensiling tropical grasses because it stimulates maximum growth of lactic acid bacteria and consequently higher lactic acid concentrations in the silage (Baskay et al, 1999;Aminah et al, 2000;Bureenok et al, 2005). At all ensiling times acetic acid concentration in unwilted silages was lower in the molasses added silage than those without molasses (Table 3).…”
Section: Resultssupporting
confidence: 82%
“…This is partly due to restricted fermentation, a lack of sufficient energy for optimal multiplication and growth of lactic acid bacteria. The present result confirms previous findings on the benefit of molasses addition when ensiling tropical grasses because it stimulates maximum growth of lactic acid bacteria and consequently higher lactic acid concentrations in the silage (Baskay et al, 1999;Aminah et al, 2000;Bureenok et al, 2005). At all ensiling times acetic acid concentration in unwilted silages was lower in the molasses added silage than those without molasses (Table 3).…”
Section: Resultssupporting
confidence: 82%
“…When the epiphytic LAB reach at least 10 5 cfu g −1 of FM, good quality silage can be made (Bureenok et al . ). In this study, LAB, aerobic bacteria, coliform bacteria, molds and yeasts were found in the native grasses and the aerobic bacteria dominated the microorganisms before ensiling.…”
Section: Discussionmentioning
confidence: 97%
“…() found no marked improvement after using lactobacillus additives in silages, whereas Bureenok et al . () reported that inoculants increased acidity and lowered the ammonia nitrogen (NH 3 ‐N) content of silages. Weinberg et al .…”
Section: Introductionmentioning
confidence: 99%